Destiny and destination the extraordinary story and history of Holy Angel University 1933-2008 - Tantingco, Robert P.; Center for Kapampangan Studies (Angeles City (Pampanga) Holy Angel University, 2009)
"This year [2008], Holy Angel University is celebrating its 75th. Its founders would probably not be surprised that the schools they put up in 1933 has lived this long. What they never could have imagined is how big it has become and how faithful it has remained to their original mission"--Book jacket.
Foreword : Holy Angel dear -- The worst times... the best of times -- The angel and the dreamers -- The faith of the founders -- The angel's playground -- Edge of the abyss -- After smoke clears, more storm clouds -- The angel takes flight -- Heading into the eye of the storm -- New university, great expectations -- Reforms and revolts -- Agony and ecstasy -- The wonder years -- Diamond year in a golden age -- Epilogue : rock of ages -- Timeline.